Stateczność płyt kompozytowych z niejednorodnym rozkładem składników - Michalak, B. (Katedra Wytrzymałości Materiałów i Konstrukcji, Politechnika Łódzka, 2003)
Celem pracy jest sformułowanie i zbadanie uśrednionego modelu opisującego stateczność płyty kompozytowej z niejednorodnym rozkładem składników. Rozpatrywana płyta ma określona budowę, która nie jest periodyczna ale która w małym obszarze rozpatrywanej płyty może być w przybliżeniu traktowana jako periodyczna. Sformułowanie przybliżonego modelu matematycznego bazuje na koncepcji uśredniania tolerancyjnego przedstawionej w pracy Woźniaka i Wierzbickiego [1 ], gdzie ciało tego rodzaju nazwane jest ciałem heteroperiodycznym.

This contribution deals with stability of certain composite plates with a deterministic materiał structure, which is not periodic, but in small regions of a plate can be approximately regarded as periodic. The formulation of approximatc mathematical models of these plates, based on the concept of what is called a tolerance averaging, was discussed in [1] where the solids of this kind where referred to as the heteroperiodic solids. In this contribution a certain approximate solutions to the periodic cell problems for the composite plates under considcration are proposed. These solutions arc based on same heuristic assumptions and lead to the system of equations with functional but slowlyvarying coefficients. It has to be mentioned that the results obtaincd in this contribution cannot be derived by using the homogenization method related to solids which are periodic with respect to a certain curvilinear parameterisation, [2]. The obtained generał results will be illustrated by an example of the selected stability problems.
Stability of composite plates with non-uniform distribution of constituents
Keywords: płyty kompozytowe; stateczność; płyta heteroperiodyczna; uśrednianie tolerancyjne; composite plates; stability; heteroperiodic plate; tolerance averaging